Physicochemical Study of the Self-Disintegration of Calcium Orthosilicate (β→γ) in the Presence of the C12A7 Aluminate Phase - Michał Pyzalski (MDPI AG, 2021)
The β-γ polymorphic transition of calcium orthosilicate (C2S) is a key phenomenon in cement chemistry. During this transition, the compound expands due to structural changes and a significant reduction in its density is observed, leading to its disintegration into a powder with a very high specific surface area. Owing to this tendency of the C2S material to “self-disintegrate”, its production is energy-efficient and thus environmentally friendly. A physicochemical study of the self-disintegration process was conducted with the aim of determining how the amount of dodecacalcium hepta-aluminate (C12A7) in calcium orthosilicate (C2S) affects the temperature at which the polymorphic transi-tions from α’L-C2S to β-C2S and from β-C2S to γ-C2S undergo stabilization. The applied techniques included differential thermal analysis (DTA), calorimetry and X-ray diffraction (XRD), and they made it possible to determine what C2S/C12A7 phase ratio in the samples and what cooling rate constitute the optimal conditions of the self-disintegration process. The optimal cooling rate for C2S materials with a C12A7 content of up to 60 wt% was determined to be 5 K·min−1. The optimal mass ratio of C2S/C12A7 was found to be 70/30, which ensures both efficient self-disintegration and desirable grain size distribution.